Differential accumulation of γ‐aminobutyric acid in elicited cells of two rice cultivars showing contrasting sensitivity to the blast pathogen. (12th February 2014) - Forlani, G.; Bertazzini, M.; Giberti, S.; Franken, P.
Abstract Intracellular free amino acid pools were quantified in suspension cultured cells of a blast‐sensitive and a blast‐resistant rice genotype at increasing times after treatment with Magnaporthe oryzae cell wall hydrolysates. Besides some expected variations in free phenylalanine, a remarkable early increase of γ‐aminobutyric acid (GABA) levels was evident in both cultivars. Glutamate decarboxylase activity and protein levels were unaffected. GABA homeostasis was recovered in the sensitive cultivar 48 h after the treatment. In contrast, a further GABA accumulation and a general increase of most amino acids was found at this later stage in the resistant genotype, which showed a larger decrease in cell viability as a consequence of elicitor addition. Data support a recently hypothesised role of GABA metabolism in the plant response to fungal pathogens.